Comparative study of phase change phenomenon in high temperature cascade latent heat energy storage system using conduction and conduction-convection models. (December 2018) - Sunku Prasad, J.; Muthukumar, P.; Anandalakshmi, R.; Niyas, Hakeem
Highlights: Thermal model is developed for predicting the performances of cascade LHTESS. Effect of convection during charging and discharging of LHTESS is demonstrated. Conduction is more dominant during discharging of LHTESS. Effect of process parameters on natural convection during phase change is studied. Abstract: In the current study, a combined conduction-convection model is developed to analyze the effect of natural convection inside the Phase Change Material (PCM) during melting and solidification processes of a cascade Latent Heat Thermal Energy Storage System (LHTESS) and it is compared with pure conduction model. Effective heat capacity method is employed to simulate the phase change phenomena in both combined model and pure conduction models. Boussinesq approximation is used to predict the effect of natural convection inside the PCM in the combined model. The governing equations involved in the model are solved using finite element based simulation software, COMSOL Multiphysics 4.3a. Parametric study is conducted on charging and discharging processes of cascade LHTESS using both the models. The comparative study between combined model and pure conduction model demonstrated that the pure conduction model under predicts the rate of heat transfer between HTF and PCM at lower inlet velocity of HTF, where natural convection plays a significant role in the phase change phenomena. The deviation between the models decreases with increase in the inlet velocity of HTF for both charging and discharging processes. The simulation results indicated that the heat transfer phenomena inside the PCM become more conduction dominant at higher inlet velocity of HTF. The results also revealed that the inlet temperature of HTF plays a major role in decreasing the charging/ discharging time.